Theology of Childhood: An Essential Element of Christian Anthropology - McEvoy, James Gerard (Irish theological quarterly, 2019)
This article argues that a consideration of children and childhood should be an essential element of theological anthropology. The argument is situated against the background of recent sociology of childhood, which emphasizes children's agency; the author offers an interpretative view of this agency. In that context, Rahner's approach to childhood in the prescient article 'Ideas for a Theology of Childhood' is examined. Finally, the author proposes a modest development of Rahner's approach by focusing on two fundamental themes of theological anthropology: children as created, and their lives as graced. A more explicit theology of childhood is indispensable for contemporary church life, especially in light of both the clergy sexual abuse crisis, and the Catholic Church's strong commitment to Catholic schooling.